2018
DOI: 10.1016/j.lithos.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine-rich amphibole in deep layered gabbros as evidence for brine/rock interaction in the lower oceanic crust: A case study from the Wadi Wariyah, Samail Ophiolite, Sultanate of Oman

Abstract: Hydrothermal veins and dykelets that cross-cut layered olivine gabbros deep in the plutonic section of the Samail Ophiolite, Sultanate of Oman, point towards the occurrence of hydrothermal circulation in the deep oceanic crust, and these features record interactions between rock and high temperature seawater-derived fluids or brines. Deep penetration of seawater-derived fluids down to 100 m above the Moho transition zone and the consequent interactions with the host rock lead to hydrothermal alteration from gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…Hydrothermal circulation at high temperatures in Wadi Wariyah is supported by observations in a well‐studied outcrop ~ 300 m south of the locality where our fine‐layered sample was taken: This outcrop of layered gabbros is characterized by a complex system of hydrothermal veins containing brown pargasitic amphibole and green magnesio‐hornblende which have formed under high to very high temperatures (850°C and 1030°C; Bosch, 2004; Wolff, 2013). Very high Cl contents in hastingsites and pargasites within these veins (up to 5 wt%, Currin et al, 2018) provide evidence for the presence of highly saline, seawater‐derived fluids at depth. Evidence for deep hydrothermal activity at high and very high temperatures in layered gabbros from fast‐spreading systems has been reported in several studies (Bosch, 2004; Garrido et al, 2001; Koepke et al, 2014; Nozaka et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Hydrothermal circulation at high temperatures in Wadi Wariyah is supported by observations in a well‐studied outcrop ~ 300 m south of the locality where our fine‐layered sample was taken: This outcrop of layered gabbros is characterized by a complex system of hydrothermal veins containing brown pargasitic amphibole and green magnesio‐hornblende which have formed under high to very high temperatures (850°C and 1030°C; Bosch, 2004; Wolff, 2013). Very high Cl contents in hastingsites and pargasites within these veins (up to 5 wt%, Currin et al, 2018) provide evidence for the presence of highly saline, seawater‐derived fluids at depth. Evidence for deep hydrothermal activity at high and very high temperatures in layered gabbros from fast‐spreading systems has been reported in several studies (Bosch, 2004; Garrido et al, 2001; Koepke et al, 2014; Nozaka et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Journal of Geophysical Research: Solid Earth 5 wt%, Currin et al, 2018) provide evidence for the presence of highly saline, seawater-derived fluids at depth. Evidence for deep hydrothermal activity at high and very high temperatures in layered gabbros from fast-spreading systems has been reported in several studies (Bosch, 2004;Garrido et al, 2001;Koepke et al, 2014;Nozaka et al, 2016).…”
Section: 1029/2020jb019573mentioning
confidence: 99%
See 1 more Smart Citation
“…Mid-Ocean Ridge vs. arc-related basin) (e.g. Bosch et al, 2004;Currin et al, 2018;France et al, 2009France et al, , 2013Gilgen et al, 2016;Python et al, 2007;Zihlmann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the Oman ophiolite, petrological and isotopic studies have shown that the crust was affected by hydrothermal circulations ranging from greenschist to upper amphibolite/granulite facies (e.g. Bosch et al, 2004;Gregory and Taylor, 1981;Koepke et al, 2005;Nehlig and Juteau, 1988;Currin et al, 2018). The formation of diopsidite and rodingite dikes likewise involves high temperature hydrothermal fluids circulating down to the Moho and even below (Akizawa et al, 2011;Python et al, 2007).…”
Section: Introductionmentioning
confidence: 99%